Mixed Spin-2 and Spin-3/2 Blume-Emery-Griffiths (BEG) Model on the Bethe Lattice - KARIMOU, Mounirou; YESSOUFOU, RACHIDI ADENIYI AKAMBI; HONTINFINDE, FÉLIX (My University, 2015)
The mixed spin-2 and spin-3/2 Blume-Emery-Griffiths (BEG) Ising ferrimagnetic system is studied by the Bethe lattice approach. The ground-state phase diagram is constructed. The influence of the crystal-field and the biquadratic interactions among neighboring spins on the thermal behaviors of the system is singled out. The system displays very rich critical behaviors with the existence of tricritical points. Compensation points where the global magnetization of the system vanishes have been detected for appropriate values of the system parameters.
Keywords: BEG Model; Tricritical Point; Compensation Points; Bethe Lattice